Comparative analysis of government management of crisis communication in Covid-19, mad cow and 11M attacks - Martínez Solana, Yolanda; Martín García, Teresa (Historia y Comunicación Social, 2021)
This article analyzes the treatment of the informative crisis of the COVID-19 from a political and health perspective, comparing it with the communication management of the emergency situations of the great environment in Spain: the ‘mad cow crisis’ and the attacks from 11M. To carry out this research, it has been done a complete chronology on COVID-19, from its origins in Wuhan. In adition, all the measures adopted by the Spanish government have been analyzed (comparing them with the recommendations of international organizations such as the World Health Organization), a comprehensive study of the main political actors involved and their comparisons to the media has been developed and the information published by the main media and other countries has been followed up.